2018
DOI: 10.20524/aog.2018.0287
|View full text |Cite
|
Sign up to set email alerts
|

Through the LAMS towards the future: current uses and outcomes of lumen-apposing metal stents

Abstract: The lumen-apposing metal stent (LAMS) is one of the revolutionary devices recently developed for gastrointestinal endoscopy. This device has a saddle-shaped design and large lumen. It was originally designed for drainage of transmural pancreatic fluid collection and in the last few years it has been used extensively for that indication. More recently, other in- and off-label indications have been proposed. Several types of LAMS are available, with or without an electrocautery-enhanced delivery system. In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 29 publications
1
52
0
1
Order By: Relevance
“…We excluded publications that did not use the 2012 Atlanta criteria for WON diagnosis, lacked information to allow evaluation of the Atlanta criteria 3 , used surgical or percutaneous drainage in addition to endoscopic drainage, represented interim analyses of ongoing studies, reported on ≤ 5 patients, or had study populations that were not mutually exclusive. With regard to LAMS, only publications that investigated the AXIOS TM stent (Boston Scientific, Marlborough, Massachusetts, United States) were included as this is the only globally available LAMS and is the LAMS most commonly described in the literature 16 . The primary analysis was limited to cases conducted under EUS guidance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded publications that did not use the 2012 Atlanta criteria for WON diagnosis, lacked information to allow evaluation of the Atlanta criteria 3 , used surgical or percutaneous drainage in addition to endoscopic drainage, represented interim analyses of ongoing studies, reported on ≤ 5 patients, or had study populations that were not mutually exclusive. With regard to LAMS, only publications that investigated the AXIOS TM stent (Boston Scientific, Marlborough, Massachusetts, United States) were included as this is the only globally available LAMS and is the LAMS most commonly described in the literature 16 . The primary analysis was limited to cases conducted under EUS guidance.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various studies assessing LAMS have published disparate safety findings, with overall adverse event (AE) rates ranging from 0 % to 50 % 9 10 11 12 . Specific adverse events (AEs) such as bleeding also have widely varying reported rates, ranging from 0 % to 25 %, with some studies (including those with small sample size) suggesting a higher rate of bleeding with LAMS compared to DPPS 9 13 14 15 16 . In addition, the relatively large variations in reported complication rates may be partially attributable to their different definitions 17 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 These include gallbladder drainage, bile duct drainage, enteroenteric anastomoses, gastrointestinal strictures, and transgastric ERCP in patients with bypass surgery. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“…This stent was originally created for pancreatic fluid collection (PFC) drainage, because of its larger inner lumen diameter than either plastic or traditional self-expanding metal stents. In addition, it allows for an endoscope to pass into PFCs to perform direct necrosectomy [29]. Over time, many additional indications have been proposed such as biliary drainage after failed ERCP [30], gallbladder drainage [31], gastroentero anastomosis [32], or for benign gastrointestinal strictures [33].…”
Section: Lumen Apposing Metal Stentsmentioning
confidence: 99%